Technology for the Production of Organomineral Fertilizers Based on Organic Resources of Plant Origin and Off-Grade Phosphorites - J.B. Hamrokulov; Sh.S. Namazov.; N.Kh. Usanbaev (American Journal of Biology and Natural Sciences, 2025)
The study investigates the process of producing fertilizers through the processing of substandard phosphorites (SP) using oxidation products of plant residues (PR) in various proportions. The following experimental conditions were examined: H₂O₂ concentration – 10%, PR:H₂O₂ ratio = 1:0.1, H₂O₂:H₂SO₄ molar ratio = 1:0.1–0.5, and phosphate raw material (PRM):PR weight ratio = 100:40–200. It was found that the treatment of phosphate raw material with oxidation products leads to a significant increase in the proportion of available (assimilable) P₂O₅ forms. The optimal conditions were determined as H₂O₂ concentration 10%, PR:H₂O₂ ratio = 1:0.1, H₂O₂:H₂SO₄ molar ratio = 1:0.5, and PRM:PR weight ratio = 100:150. The commercial properties of the resulting fertilizers—hygroscopicity, moisture capacity, caking tendency, and granule strength—were evaluated, and X-ray diffraction analysis was performed. Based on the results, a technological process was proposed and a material balance for the production of fertilizers using oxidized PR in the presence of sulfuric acid was calculated.